Perda de solo, água, carbono orgânico e nutriente por erosão hídrica em diferentes cultivos e savana natural no norte da Amazônia - Souza, Fernando Gomes de (2014)
Water erosion is a major cause of land degradation in Brazil and worldwide, causing serious damage in the physical, chemical and biological soil properties, and promote the reduction of infiltration capacity of the soil water, and directly affect the agricultural productivity. In this context, this study aimed to determine the loss of soil, water, nutrients (Ca2+, Mg2+, K+ and P) and organic carbon in different cultures, bare soil and natural savannah, under natural rainfall. The experimental design was a completely randomized design with five treatments (bare soil - SD, cowpea - CF Brachiaria brizantha - BB Corn - MI and natural savannah - SN) and two repetitions. Large losses of soil and water occurred in bare soil , followed by soil cultivated with cowpea; Soils under Brachiaria brizantha, Corn and Natural Savannah were more effective in reducing the loss of soil and water during all months evaluated; The month of August showed erosive rainfall over the months of June and July; The greatest losses of Ca2+ and Mg2+ occurred in the month June, with the largest losses of Ca2+ occurred in the treatment of CF with 0.206 kg ha-1, followed by SD with 0.103 kg ha-1 and MI with 0.114 kg ha-1 for Mg2+ the greatest losses were observed in the treatment of SD with 0.270 kg ha-1 followed by FC with 0.161 kg ha-1; The control of nutrient losses and organic carbon was more effective in the treatments with Brachiaria brizantha - BB Corn - Natural and MI Savannah - SN; The biggest losses P and K+ occurred in the treatment of CF with 0.248 kg ha-1 P at the beginning of vegetative growth, and 0.006 kg ha-1 of K+ during growth. Losses of phosphorus and potassium treatments followed in their wake CF > SD > MI > SN > BB; The greatest losses of CO occurred in the month of August, the month of greatest rainfall for the treatment of erosive SD with 1.875 kg ha- 1 rain.